2011
DOI: 10.1364/ao.50.000710
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength multiplexing multiple-image encryption using cascaded phase-only masks in the Fresnel transform domain

Abstract: We propose a method of wavelength multiplexing based on a modified Gerchberg-Saxton algorithm (MGSA) and a cascaded phase modulation scheme in the Fresnel transform domain to reduce the cross talk in the multiple-image-encryption framework. First, each plain image is encoded to a complex function by using the MGSA. Next, the phase components of the created complex functions are multiplexed with different wavelength parameters, and then they are modulated before being combined together as a phase-only function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 27 publications
(50 reference statements)
0
52
0
Order By: Relevance
“…3,[5][6][7][8] MIE based on wavelength multiplexing was to synthesize the final image by superimposing individual encrypted images together. This encryption strategy was time-consuming and sensitive to cross talk noise from adjacent images.…”
Section: Multiple Image Encryptionmentioning
confidence: 99%
“…3,[5][6][7][8] MIE based on wavelength multiplexing was to synthesize the final image by superimposing individual encrypted images together. This encryption strategy was time-consuming and sensitive to cross talk noise from adjacent images.…”
Section: Multiple Image Encryptionmentioning
confidence: 99%
“…In addition, the encryption capacity is also limited in these encryption methods. To overcome the cross-talk problem and increase encryption capacity, many improved multiple-image encryption techniques have been proposed [14][15][16][17][18][19][20][21]. In the encryption process of these improved methods, all images to be encrypted are required to be encoded separately into one or more phase-only masks with all kinds of phase retrieval algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al 22 proposed a multiple-image encryption and multiplexing approach based on a modified GerchbergSaxton algorithm (MGSA) in the FrT domain, which reduces the cross-talks significantly. Chang et al 23,24 also suggested the position multiplexing encryption using cascaded phaseonly masks based on the MGSA.…”
Section: Introductionmentioning
confidence: 99%